REHABILITASI SALURAN DRAINASE DESA LIANG KECAMATAN SALAHUTU KABUPATEN MALUKU TENGAH - Glen Boyke Rehatta; Semuel Uneputty (Jurusan Teknik Sipil, 2022)
The performance of drainage channels is very important to ensure the flow of water from upstream to downstream. Likewise with drainage channels in the village of Liang, Salahhutu sub-district, Central Maluku Regency. From the results of a previous study by the author regarding the capacity of the existing canals in Liang Village, there are several canals whose capacity will not be able to hold water in the next 10 years. The channels are channels K3 – K8 where the channel Planned Debit (Qr) > Existing Debit (QS). Therefore this study aims to rehabilitate the dimensions of the existing canal so that in the next 10 years the drainage canal in Liang village will be able to function properly. This research rehabilitates the dimensions of the existing canal so that its capacity can be increased. The results of the research are as follows; Channel K3 : Qr (2.598 m3/s) < Qs(4.8751m3/s). Channel K4 : Qr (2.0922 m3/sec) < Qs (2.2890 m3/sec), Channel K5 : Qr (2.21 m3/sec) < Qs (2.6526 m3/sec), Channel K6 : Qr (1.5119 m3/sec) < Qs (1.9813 m3/sec), Channel K7 : Qr (1.99 m3/sec) < Qs (2.0990 m3/sec), Channel K8 : Qr (2.25 m3/s) < Qs (3.2493 m3/s).